Exploring Teacher Identity and Psychological Dynamics through Freudian Analysis: A Case Study of The Teacher’s Diary (2014) - Budiman, Muhammad Arief; Angelusia Amanda Fatin (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study examines the psychological dynamics of teachers as portrayed in the Thai film “The Teacher’s Diary” (2014) using Freud’s psychoanalytic theory of id, ego, and superego, alongside defense mechanisms. The research employs qualitative content analysis, focusing on key scenes that reveal the emotional, moral, and reflective behaviors of the main characters, Song and Ann. Results indicate that both teachers manage internal conflicts and external challenges through rationalization, sublimation, intellectualization, and moral commitment, demonstrating resilience, reflective practice, and ethical awareness. The discussion connects these findings with contemporary theories of effective teaching, emphasizing emotional intelligence, moral purpose, and reflective practice as core competencies for teacher development. The study highlights how cinematic narratives can provide valuable insights into teacher identity, professional growth, and the integration of personal and professional competencies in education.